1982
DOI: 10.1161/01.hyp.4.6.773
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the sympathetic nervous system to the hypertensive effect of a high sodium diet in stroke-prone spontaneously hypertensive rats.

Abstract: SUMMARY In stroke-prone spontaneously hypertensive rats (SHRSP) plasma norepinephrine levels and vascular reactivity to norepinephrine are increased and intravascular volume is reduced during the developmental phase of hypertension. Since the accelerated rise in blood pressure following sodium-loading in SHRSP cannot be attributed to the volume-retaining properties of sodium, the effects of an increased dietary intake of sodium on biochemical parameters of sympathetic vascular tone were investigated. The follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
15
0

Year Published

1984
1984
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 36 publications
4
15
0
Order By: Relevance
“…24 -" Elevation of the plasma level of norepinephrine has been reported in the former, 26 and intracerebroventricular administration of 6-hydroxydopamine prevented the DOCAinduced hypertension and increase in plasma norepinephrine. 27 On the contrary, our observations are consistent with reports of no increase in norepinephrine in saline-loaded Wistar rats 28 and of a decrease in norepinephrine in metyraponeinduced hypertensive dogs. 8 The discrepancy between these findings may be due to differences in the species used and the rapidity of volume expansion.…”
Section: Figure 4 Relationship Between Change In Pressor Response Tosupporting
confidence: 92%
“…24 -" Elevation of the plasma level of norepinephrine has been reported in the former, 26 and intracerebroventricular administration of 6-hydroxydopamine prevented the DOCAinduced hypertension and increase in plasma norepinephrine. 27 On the contrary, our observations are consistent with reports of no increase in norepinephrine in saline-loaded Wistar rats 28 and of a decrease in norepinephrine in metyraponeinduced hypertensive dogs. 8 The discrepancy between these findings may be due to differences in the species used and the rapidity of volume expansion.…”
Section: Figure 4 Relationship Between Change In Pressor Response Tosupporting
confidence: 92%
“…Potassium might interfere with a number of mechanisms that have been implicated in the adverse effects of high sodium intake in SHRSP. Such mechanisms include changes in extracellular fluid volume, 7 activation of central or autonomic nervous system, 8 " 10 enhanced vascular reactivity to pressor agents, 11 Previous research from our laboratory has defined the effects of dietary potassium deprivation and administration on plasma renin activity (PRA) in both animals 18 and human subjects. 19 We also detected a positive correlation between PRA and the development of stroke and heart attack in humans.…”
mentioning
confidence: 99%
“…8 "" Although the precise mechanism of the antihypertensive action of KCI remains controversial, its natriuretic properties are thought to play an important role. 10 ' 2 13 Moreover, recent reports have indicated that dietary KCI supplementation decreased plasma norepinephrine concentration in NaCl-loaded hypertensive rats 14 and improved baroreceptor function in hypertensive rats 15 and humans. 16 Taken together, there is a considerable possibility that KCI may change the sympathetic nerve activity, leading in turn to the natriuresis and resultant attenuation of the rise in blood pressure with NaCl loads in hypertensive patients.…”
mentioning
confidence: 99%